Math 317: Linear Algebra Worksheet 1: 1.1,1.2,1.4 Fall 2015 Name: 1. (a) Suppose that x, y ∈ Rn are nonparallel vectors. Prove that if sx + ty = 0 then s = t = 0. (Hint: It may be useful to use contradiction here. That is, assume that either s 6= 0 or t 6= 0, and show that this is impossible by contradicting the original hypothesis.) Proof: Suppose by way of contradiction that s 6= 0. (We will later see that the same argument works if we assume that t 6= 0 instead.) There are two cases to consider. First, if t = 0, then sx + ty = sx = x = 0, since s 6= 0. Since one of the vectors is 0, then x and y are neither parallel nor nonparallel, contradicting the hypothesis that x, y ∈ Rn are nonparallel vectors. Now let us suppose that t 6= 0. Then sx+ty = 0 =⇒ sx = −ty =⇒ x = − st y, which says that x is parallel to y, (since x is a constant multiple of y, i.e x = cy with c = − st . This is a contradiction to the hypothesis which states that x, y ∈ Rn are nonparallel vectors. Thus s = 0. The argument works the same way if t 6= 0. Thus, s = t = 0. (b) Use (a) to prove that if ax + by = cx + dy, then a = c and b = d. Proof: Once again, we assume that x, y ∈ Rn are nonparallel vectors. Then ax + by = cx + dy =⇒ (a − c)x + (b − d)y = 0. But from part (a), we know that a − c = 0 =⇒ a = c and b − d = 0 =⇒ b = d. 2. Using only those properties in Section 1.1, Problem 28, prove that if a + c = b + c for some vectors a, b, c ∈ Rn , then a = b. This is the cancellation property that some of you used (without proof) in your homework assignment. Proof: To prove that a + c = b + c for some vectors a, b, c ∈ Rn =⇒ a = b, we use properties 28(b) and 28(d). 28(d) tells us that there is an element, call it −c such that c + (−c) = 0. Using this fact, along with the associativity property in 28(b), we obtain: a + (c − c) = b + (c − c) =⇒ a + 0 = b + 0 =⇒ a = b by 28(c). 1 Math 317: Linear Algebra Worksheet 1: 1.1,1.2,1.4 Fall 2015 3. Let u, v ∈ Rn and suppose that u − v is orthogonal to u + v. Prove that u and v have the same magnitude. Proof : Suppose that u−v is orthogonal to u+v. Then (u − v)·(u + v) = 0. Using the associated properties of dot product, we obtain: (u − v) · (u + v) = = = = u·u+u·v−u·v−v·v u·u−v·v kuk2 − kvk2 0. Thus, kuk2 = kvk2 =⇒ kuk = ±kvk =⇒ kuk = kvk since kuk ≥ 0, kvk ≥ 0. Thus u and v have the same magnitude. 4. (a) For some x ∈ Rn , show that x · y = x · z does not necessarily imply that y = z by coming up with a suitable example. (Suggestion: Look for examples in R2 . Is it possible for a vector x to be orthogonal to two different vectors? ) Following the suggestion above, we look for examples in R2 . Let x = (1, 2). We look for a vector y that is orthogonal to x. (You certainly don’t have to use this approach, but this is a nice way to come up with an example for the problem above.) If y is orthogonal to x = (1, 2) then (1, 2) · y = 0 =⇒ (1, 2) · (y1 , y2 ) = 0 =⇒ y1 + 2y2 = 0. From here there are many values for y1 and y2 that we can pick which will satisfy this equation. One set of values will serve as a vector for y and another set of values will serve as a vector for z so that x·y = x·z = 0. We see here that y = (2, −1) and z = (4, −2) will get the job done. (b) Suppose that x · y = x · z for all x ∈ Rn . Show that y = z. Proof: Suppose that x · y = x · z for all x ∈ Rn . We want to show that y = (y1 , y2 , . . . , yn ) = z = (z1 , z2 , . . . , zn ) which is equivalent to show that y1 = z1 , y2 = z2 , . . . yn = zn . Let x1 = (1, 0, . . . , 0). Then x1 ·y = x1 ·z =⇒ 1y1 +0y2 +. . .+0yn = 1z1 +0z2 +. . .+0zn =⇒ y1 = z1 . We see that we can do this for each component of y and z. For i = 1, 2, . . . , n, let xi = (0, 0, . . . , 1, . . . , 0) where 1 is the ith element of the vector xi . Then xi · y = xi · z =⇒ 0y1 + 0y2 + . . . + 1yi + . . . 0yn = 0z1 + 0z2 + . . . + 1zi + . . . + 0zn =⇒ yi = zi . Since this true for each i = 1, 2, . . . , n, then y = z. 5. Determine if (3, 4, −1, 6) lies in span {(1, 2, −1, 2), (−2, 3, 1, −1), (−1, 3, 2, 1)}. 2 Math 317: Linear Algebra Worksheet 1: 1.1,1.2,1.4 Fall 2015 Recalling that span {(1, 2, −1, 2), (−2, 3, 1, −1), (−1, 3, 2, 1)} is the set of all linear combinations of (1, 2, −1, 2), (−2, 3, 1, −1), (−1, 3, 2, 1), asking if (3, 4, −1, 6) lies in span {(1, 2, −1, 2), (−2, 3, 1, −1), (−1, 3, 2, 1)} is equilvalent to asking if there are constants c1 , c2 and c3 such that 3 1 −2 −1 4 2 3 3 = c1 + c2 + c3 . 1 −1 1 2 6 2 −1 1 This is equivalent to the following system of equations: 3 4 1 6 = = = = c1 − 2c2 − c3 2c1 + 3c2 + 3c3 −c1 + c2 + 2c3 2c1 − c2 + c3 . We can write this system of equations in matrix form as follows: 1 −2 −1 3 c1 2 3 3 4 c = −1 1 2 2 1 c3 2 −1 1 6 To solve this system of equations, we can put this system in augmented matrix form and find its corresponding reduced row echelon form. The augmented matrix [A|b] is given as 1 −2 −1 3 2 3 3 4 . −1 1 2 1 2 −1 1 6 We row reduce the augmented matrix, starting with 1 (boxed in) as our pivot entry and making each entry (in the same column) below 1 a zero. [1] −2 −1 3 2 3 3 4 3 →R3 R1 +R −→ −1 1 2 1 −2R1 +R2 →R2 −2R1 +R4 →R4 2 −1 1 6 1 −2 −1 3 0 [7] 5 −2 (1/7)R2 →R2 −→ 0 −1 1 4 0 0 3 3 3 Math 317: Linear Algebra Worksheet 1: 1.1,1.2,1.4 1 −2 −1 3 0 [1] 5/7 −2/7 R2 +R3 →R2 −→ 0 −1 1 4 −3R2 +R4 →R4 0 0 3 3 Fall 2015 1 −2 −1 3 0 1 5/7 −2/7 3 +R4 →R4 −(1/2)R−→ 0 0 [12/7] 26/7 6/7 0 0 6/7 1 −2 −1 3 0 1 5/7 −2/7 0 0 12/7 26/7 0 0 0 −1 The last row in our augmented matrix is equlivalent to 0c1 + 0c2 + 0c3 = −1 which doesn’t make any sense. Thus, this system is inconsistent and so there is not a set of scalars c1 , c2 and c3 so that b is a linear combination of (1, 2, −1, 2), (−2, 3, 1, −1), (−1, 3, 2, 1). 6. Determine the reduced row echelon form of A and give the solution to Ax = 0 in standard form. 2 −2 4 A = −1 1 −2 3 −3 6 We can simultaneously solve Ax = 0 and find the reduced row echelon form of A by starting with the coorsponding augmented matrix [A|0]. [2] −2 4 0 1 →R1 −1 1 −2 0 (1/2)R −→ 3 −3 6 0 [1] −1 0 0 0 0 [1] −1 2 0 R1 +R2 →R2 −1 1 −2 0 −→ −3R1 +R3 →R3 3 −3 6 0 2 0 0 0 0 0 From the reduced row echelon form of A we see that x1 is our pivot variable and x2 , x3 are our free variables. From the first equation, we have that x1 − x2 + 2x3 = 0 =⇒ x1 = x2 − 2x3 . In standard form, the solution becomes x1 x2 − 2x3 x2 −2x3 1 −2 x2 = x2 = x2 + 0 = x2 1 + x3 0 x3 x3 0 x3 0 1 Note that this says that the solution set to Ax = 0 is precisely span {(1, 1, 0), (−2, 0, 1)}. 4